Decomposing Figures Rhetorical Readings in the Romantic Tradition - Chase, Cynthia (Johns Hopkins University Press, 2019)
Originally published in 1986. The ghastly fate of a drowned man brought to a lake's surface in Wordsworth's "Prelude" typifies a fundamental pattern in Romantic writing, argues Cynthia Chase. Disfiguration involves not only a departure from representation but a disruption of the logic of figure or form, a decomposition of the figures composing the text. Ultimately it manifests the conflict between a work's meaning and its mode of performance. By means of an intense engagement with texts in the romantic tradition, Decomposing Figures rearticulates and recasts crucial concepts in recent literary theory, including the notion of the self-referential or self-reflexive nature of the literary work. Chase's readings show that, far from implying a privileged status, the work's self-reflexive structure entails its opacity, its inability to read itself, and the necessity of its decomposition.